THE PRINCIPLES OF SINGLE EUROPEAN SKY PROGRAM IMPLEMENTATION IN UKRAINE - Kharchenko, Volodymyr P.; Chynchenko, Yuriy V.; Babeichyk, Dmitriy G.; Bugayko, Dmitro O. (Proceedings of National Aviation University (archive), 2009)
The principles of Single European Sky programme implementation process, contents of European Master Plan, deployment process of the Single European Sky target concept and Single European Sky performance targets are considered.